Produksi Katup Mesin Diesel Tipe TS70/80, Silinder 500 cm3, fBatang 7x105 mm, Kapasitas 1 Biji/Jam (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
The unavailability of intake and exhaust valves for 500 cm³ diesel engines manufactured in the 1980s has created difficulties in maintaining and operating agricultural tractors. This study aimed to manufacture replacement intake and exhaust valves using SUH 35 austenitic steel according to the original engine specifications. The production process included design preparation, material selection, raw material measurement, forging, machining, heat treatment, quality inspection, and packaging. SUH 35 steel rods measuring 12 mm in diameter and 105 mm in length were used as the raw material. Forging was performed to form the valve heads, producing exhaust valves with a diameter of 30 mm and thickness of 2 mm, and intake valves with a diameter of 35 mm and thickness of 2.5 mm. After machining, the final dimensions of the exhaust valve were 29.5 mm head diameter, 2 mm thickness, 105 mm length, and 7 mm stem diameter, while the intake valve measured 33.5 mm head diameter, 2.5 mm thickness, 105 mm length, and 7 mm stem diameter. Hardening treatment produced a hardness value of 40 HRC. The manufactured valves met the required dimensional and mechanical specifications. The production cost was IDR 100,000 per unit, with a processing time of approximately 60 minutes per unit. The results demonstrate that replacement valves for 500 cm³ diesel engines can be successfully reproduced, enabling the continued operation and maintenance of older tractor engines.